Clinical Outcomes and Predictors of Satisfaction in Patients with Improved Lithium Disilicate All-Ceramic Crowns - Samer, M.S.; Faraz, Q.; Al-Dubai, S.A.R.; Vohra, F.; Abdullah, H.; Taiyeb-Ali, T.B.; Saub, R. (Karger Publishers Open Access, 2017)
Objectives: The aim of this study was to determine the clinical outcomes and predictors of satisfaction in patients with lithium disilicate (LD) ceramic crowns. Subjects and Methods: Clinical outcomes were assessed in 47 patients with 88 LD crowns using modified United States Public Health Service (USPHS) evaluation criteria and survival rates. The questionnaire for predictors included 3 aspects: (a) sociodemographic characteristics, (b) oral health habits (tooth brushing frequency, flossing frequency, and dental visits), and (c) satisfaction of the restorations (aesthetics, function, fit, cleansability, and chewing ability of the crowns, and overall satisfaction). Frequency distributions were computed using univariate and multivariate analysis. The Student t test and analysis of variance (ANOVA) were used to compare means across variables. Correlation analysis was done to assess the association between continuous variables. Results: The age of crowns was 34.7 ± 9.7 months. The survival rate was 96.6% at 35.9 ± 9.2 months. There was a significant association between successful crown function and oral hygiene measures: tooth brushing (p 0.001), dental visits (p = 0.006), and flossing (p = 0.009). A strong negative correlation was observed between aesthetic satisfaction (r = -0.717, p 0.001) and chewing ability (r = -0.639, p 0.001) with crown age. The linear regression model was significant for all predictors (p < 0.05) except overall satisfaction (p > 0.05). Conclusion: The LD crowns had long survival rates of 96.6% up to 35.9 ± 9.2 months and provided satisfactory clinical performance (low risk of failure). Oral hygiene habits such as brushing, flossing, and regular dental visits influenced patient satisfaction with LD crowns.